Digitalisasi Usaha Berbasis Iman : Bimtek E-Commerce dalam Perspektif Sosiologi Agama di Papua - Melda Agnes Manuhutu; Natasya Virginia Leuwol; Ferdinan Ferdinan; Salomo Salomo; Arjuna Arjuna; Maria Maria; Wilfrida Wilfrida; Lulu Jola Uktolseja (Pelayanan Unggulan : Jurnal Pengabdian Masyarakat Terapan, 2025)
This technical guidance (bimtek) activity was held with the primary objective of improving the digital capacity of Micro, Small, and Medium Enterprises (MSMEs) members of the Papua Gallery in Sorong City. The approach used was quite unique because it combined information technology, specifically the e-commerce platform Odoo, with a sociological perspective of religion. This approach places the values of faith, community ethics, and local culture as the main foundation in the digital transformation process being carried out. This activity was carried out by a team of lecturers from Victory University Sorong from the Information Systems and Sociology of Religion Study Program, and involved students as part of community service. The implementation process included several stages: an assessment of MSMEs' digital needs, technical training on using Odoo, direct assistance in implementing the dare store, evaluation of results, and ongoing follow-up. The results of the activity showed a significant increase in digital literacy among MSMEs, success in creating and managing online stores independently, and a growing awareness that business digitization is not only an economic necessity, but also part of spiritual and social responsibility. In addition, this activity also helped strengthen the branding and presence of local Papuan culture through digital media. This faith- and cultural-based training model has proven effective and relevant for replication in other MSME communities in different regions, especially those with strong local cultural and religious potential.